Two Strategies for Inductive Reasoning in Organizational Research - Ketokivi, Mikko; Mantere, Saku (Academy of Management Review, 2010)
Incompleteness of inductive reasoning presents an enduring dilemma for organizational researchers. We examine two practical reasoning strategies—idealization and contextualization—that can be used at the pinnacle of this dilemma: when theoretical conclusions are drawn from empirical data. Understanding the two strategies can lead to more effective argumentation and evaluation. Appreciating the methodological incompleteness of both strategies, in turn, helps us distinguish between the methodological and the policy dimensions of organization-scientific debates.